SIGNIFICANCE OF MAIN MONUMENTS IN HISTORICAL DISTRICTS OF ODESSA AND ST. PETERSBURG FOR PERCEPTION OF THESE CITIES - Ivan Savchuk (Geography, Environment, Sustainability)
This paper analyses the significant role of the monuments of historical districts of two major cities in Russia and Ukraine in perception of their images by people. Certain historical monuments and artifacts of Odessa and St. Petersburg have been used by official ideology and propaganda in creating of clear associations-clichés. It has been achieved through the conscious use of color combinations, lush décor, careful placement of the monuments, etc. Future research activities in this field should involve further investigation of the role of locations of socially important historical buildings and analysis of the role of various images of the city and its individual components in fiction and popular tourist literature. These efforts will facilitate holistic understanding of the value of entire cities, as well as of their individual components to collective mentality and to the public policy and ideology.